The sustainability of health care systems in Europe - Baltagi, Badi H.,; Moscone, Francesco, (Contributions to economic analysis ;)
This volume contains an Open Access Chapter 'The Sustainability of Health Care Systems in Europe' provides a comprehensive understanding of the sustainability of health systems in Europe. Furthermore, it includes an introduction to how EU action in supporting health- care policies in the EU Member States, looking both at implemented actions and describing current priorities for the future. There has been a rapid evolution of the structure of society and the economy over the last few decades which has created new demands for healthcare services. This has placed pressure on policy makers to ensure the sustainability of the health care sector. Policy makers understand the efficiency of the healthcare delivery system needs to be improved, the shortage of health professionals must be tackled, and that there are growing health inequalities and inequity in access to healthcare. These challenges are exacerbated by recent economic shocks including the 2008 recession, the uncertainty related to Brexit, and the crisis induced by the COVID-19 pandemic, which have impacted the ability of European health systems to finance the health care sector. This book is a must read for researchers and students of health economics and health policy.